IDNLearn.com: Your trusted platform for finding reliable answers. Discover thorough and trustworthy answers from our community of knowledgeable professionals, tailored to meet your specific needs.
Sagot :
To solve the equation [tex]\(-\frac{1}{2} n^2 + 18 = 0\)[/tex], follow these steps:
1. Rewrite the equation in standard quadratic form [tex]\(ax^2 + bx + c = 0\)[/tex]:
[tex]\[ -\frac{1}{2} n^2 + 18 = 0 \][/tex]
2. Move the constant term to the other side of the equation by subtracting 18 from both sides:
[tex]\[ -\frac{1}{2} n^2 = -18 \][/tex]
3. Multiply both sides by [tex]\(-2\)[/tex] to eliminate the fraction:
[tex]\[ n^2 = 36 \][/tex]
4. Take the square root of both sides to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \pm \sqrt{36} \][/tex]
5. Simplify the square root:
[tex]\[ n = \pm 6 \][/tex]
So, the solution of the equation is:
[tex]\[ n = \pm 6 \][/tex]
1. Rewrite the equation in standard quadratic form [tex]\(ax^2 + bx + c = 0\)[/tex]:
[tex]\[ -\frac{1}{2} n^2 + 18 = 0 \][/tex]
2. Move the constant term to the other side of the equation by subtracting 18 from both sides:
[tex]\[ -\frac{1}{2} n^2 = -18 \][/tex]
3. Multiply both sides by [tex]\(-2\)[/tex] to eliminate the fraction:
[tex]\[ n^2 = 36 \][/tex]
4. Take the square root of both sides to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \pm \sqrt{36} \][/tex]
5. Simplify the square root:
[tex]\[ n = \pm 6 \][/tex]
So, the solution of the equation is:
[tex]\[ n = \pm 6 \][/tex]
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.